The Influence of Financial Literacy and Risk Perception on Interest in Using Paylater in Communities of Waru, Sidoarjo District - Sadiqin, Amin (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Paylater is a financial product, and its use can be influenced by a person's literacy level. A person's interest in using a financial product can be influenced based on an understanding of financial concepts called financial literacy and also knowledge of these risks.This research is descriptive research with quantitative methods.The results of this research state that the variables financial literacy (X1) and risk perception (X2), both partially and simultaneously, have a positive and significant effect on interest in using (Y) paylater in the people of Waru, Sidoarjo District.